The prevalence and determinant factors of substance use among the youth in Ethiopia: A multilevel analysis of Ethiopian Demographic and Health Survey - Kassew, Tilahun; Tarekegn, Gebrekidan Ewnetu; Alamneh, Tesfa Sewunet; Kassa, Selam Fisiha; Liyew, Bikis; Terefe, Bewuketu (Frontiers in Psychiatry, 2023)
Background: In Ethiopia, the youth are more exposed to substances like alcohol, Khat, and tobacco than other populations. Despite the seriousness of the situation, low and middle-income nations, particularly Ethiopia, have intervention gaps. Service providers must be made more aware of relevant evidence to combat this. This research focused on finding out how common substance abuse is among teenagers and what factors influence it. Methods: The 2016 Ethiopian demographic and health survey data were used in secondary data analysis. This survey includes all young people aged 15 to 24. The total weighted sample size was 10,594 people. Because of the hierarchical nature of the Ethiopian demographic and health survey data, a multilevel logistic regression model was employed to uncover individual and community-level characteristics related to substances. Results: In Ethiopia, the overall current prevalence of substance use occasionally or daily in the preceding 30 days of the survey was 46.74%. Of the participants, 36.34%, 12.56%, and 0.95% were drinking alcohol, chewing Khat, and smoking cigarettes/ any tobacco products, respectively. Male sex, 20-24 years of age, individual’s media exposure, having job, and living in large central and metropolitan regions were the factors associated with the problem. Conclusion: According to the 2016 EDHS survey, the youth people who consume substances were widespread in Ethiopia. To lower the prevalence of substance use among youth people, policymakers must increase the implementation of official rules, such as restricting alcohol, Khat, and tobacco product marketing to minors, prohibiting smoking in public places, and banning mass-media alcohol advertising. Particular interventions targeting at-risk populations, such as youth, are mainly required in prominent central and metropolitan locations.